The Role of Village-Owned Enterprises (BUMDES) in Improving the Economy of Village Communities in the Field of Micro Enterprises in Sindanglaut Village, Carita District, Pandeglang Regency - R, Moh Arif Mulyawan; Gunawan, Ernawati (CV. Lenggogeni Data Publishing, 2024)
This study aims to analyze the role of the Village-Owned Enterprise (BUMDes) in improving the village community’s economy, particularly in the microenterprise sector of Sindanglaut Village, Carita District, Pandeglang Regency. This research employs a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings indicate that BUMDes Sindanglaut has played an essential role in promoting local economic growth through several business units. However, several challenges persist, including limited business capital, insufficient human resource capacity, low community participation, and a lack of awareness regarding the importance and benefits of BUMDes. Consequently, some business units, such as the savings and loan unit, have become inactive. On the other hand, three business units—event equipment rental, agricultural and plantation product trading—remain active and contribute positively to the local economy. The sustainability of these units is supported by government assistance, abundant natural resources, and private sector collaboration. To address the existing obstacles, this study suggests implementing training and socialization programs for both BUMDes managers and community members to enhance skills and participation. Strengthening human resources and collective involvement are crucial for ensuring the success and sustainability of BUMDes as a driver of rural economic empowerment.